Predictors of Mortality in Children Admitted with Severe Pneumonia - Rabia Tariq, Tabinda Noreen, Sundas Ikram, Naushin Maqsood (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To explore clinical and laboratory markers of mortality in children with severe pneumonia on admission and evaluate their effect on mortality. Place and Duration of Study: The study was conducted in the paediatrics department of Mayo Hospital Lahore from November 2022 to April 2023. Methodology: Children aged between 2 months, and 5 years admitted with severe pneumonia were evaluated using a cross-sectional analysis study that was based on the WHO criteria. The WHO sample size calculator was used to calculate the sample size. There were 150 enrolled patients using non-probability consecutive sampling. Each patient was recorded in terms of detailed patient history, clinical examination, and pertinent laboratory investigations (including complete blood count, oxygen saturation and chest radiography). The essential variables that were investigated included the age, gender, nutritional state, existence of comorbidities, hypoxia, and mechanical ventilation necessity. The patients were strictly observed and tracked during their hospitalization to identify clinical outcomes, which were recovery or death (mortality). Results: Among the number of patients who were enrolled, it was found that X% died. The severe malnutrition, hypoxia (SpO 2 below 90 percent), late arrival to the hospital, the presence of sepsis, and the need to put a person on the ventilator, were significant predictors of mortality (p < 0.05). Incomplete immunization and younger age (below 1 year old) were also risk factors that contributed to the probability of death. The mortality rate of patients who came with several risk factors was also considerably higher than that of patients with limited complications. Conclusion: The causes of child mortality due to severe pneumonia have been high especially in patients who are malnourished, hypoxic and delayed in receiving the treatment. To improve the survival rates, it may be effective to detect the high-risk patients early and provide timely care. To reduce the burden of the disease, it is vital to reinforce preventive strategies, including immunization and early referral. Keywords: Severe pneumonia, children, mortality predictors, paediatric patients, hypoxia, malnutrition, comorbidities, mechanical ventilation, risk factors, clinical outcomes. Keywords: Severe pneumonia, mortality predictors, hypoxia, malnutrition, comorbidities, mechanical ventilation, clinical outcomes